MODEL BOX- JENKINS DALAM RANGKA PERAMALAN PRODUK DOMESTIK REGIONAL BRUTO PROVINSI BALI - Suryana Utama, Made; Nata Wirawan, I Gusti Putu (Buletin Studi Ekonomi; VOL.19.NO.1.FEBRUARI 2014.(PP 1-117), 2016)
Box-Jenkins Models in the Framework to Forecast Bali Province Gross Domestic Product. Gross Domestic Product ( GDP ) is the most widely used indikator of development. In order to make development plan of an area with effective and responsible principal, it required a valid estimate of GDP. The presence of relatifly large gap between targets and achievements of the Bali Provincial economic growth during 2008-2012, and given the importance of GDP as an indikator of regional economic performance, it is necessary to do research on the application of Box-Jenkins models in order to forecast Bali Province GDP. This study aims to create a model of the Bali Provincial GDP estimates using data from the first quarter of GDP in 2000 to fourth quarter of GDP in 2012 with constant prices of 2000, which is sourced from BPS of Bali Province. The analysis technique is applied to the Box- Jenkins models or Autoregresive Integreted Moving Average (ARIMA).The results showed that by using the data of Bali Provincial GDP first quarter of 2000 to the fourth quarter of 2012, concluded that the best model to use as a forecast model is ARIMA (2,1,0).   Keywords : GDP , Autoregresive Integreted Moving Average
Keywords: GDP , Autoregresive Integreted Moving Average